Clause Complex Analysis in CNN and Reuters News Reports: A Systemic Functional Linguistics Perspective - Chalimatuz Zahro; Afanda Tiara Sari; Chalimah Chalimah (Journal of Cultural Narratives in Digital Society, 2026)
Within Systemic Functional Linguistics (SFL), clause complex relations play an important role in organizing information and constructing meaning in discourse. While previous studies have primarily focused on identifying and classifying clause complex patterns, limited attention has been given to how such grammatical choices reflect communicative purposes in news reporting. Therefore, this study investigates the clause complex structures employed in CNN and Reuters news reports concerning the trade agreement between Indonesia and the United States. Specifically, the study aims to identify interdependency relations and logical-semantic relations, compare the clause complex patterns used by both news organizations, and explain how these patterns reflect different journalistic communication strategies. Using a qualitative descriptive approach, the study analyzed two online news reports through Halliday and Matthiessen’s (2014) clause complex framework. The findings revealed that hypotaxis was the dominant interdependency relation, occurring 34 times in CNN and 10 times in Reuters, while enhancement and projection: locution were the most frequent logical-semantic relations, each occurring 19 times. The results suggest that both news organizations employed clause complex structures to contextualize events and support source attribution. However, CNN utilized more hypotactic constructions and contextual explanations, indicating a tendency toward explanatory reporting, whereas Reuters emphasized concise reporting through direct presentation of facts and official statements. These findings demonstrate that clause complex relations function not only as grammatical resources but also as strategic communicative tools through which journalists organize information and shape audience interpretation. The study contributes to clause complex research by extending the analysis from structural description to the examination of communicative functions in international news discourse. This study contributes to media discourse studies by demonstrating that clause complex relations function not only as grammatical resources but also as strategic communicative tools that shape audience interpretation in economic news reporting.